Identification of Cadherin 2 (CDH2) Mutations in Arrhythmogenic Right Ventricular Cardiomyopathy. (April 2017) - Mayosi, Bongani M.; Fish, Maryam; Shaboodien, Gasnat; Mastantuono, Elisa; Kraus, Sarah; Wieland, Thomas; Kotta, Maria-Christina; Chin, Ashley; Laing, Nakita; Ntusi, Ntobeko B.A.; Chong, Michael; Horsfall, Christopher; et al.
Abstract : Background—: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically heterogeneous condition caused by mutations in genes encoding desmosomal proteins in up to 60% of cases. The 40% of genotype-negative cases point to the need of identifying novel genetic substrates by studying genotype-negative ARVC families. Methods and Results—: Whole exome sequencing was performed on 2 cousins with ARVC. Validation of 13 heterozygous variants that survived internal quality and frequency filters was performed by Sanger sequencing. These variants were also genotyped in all family members to establish genotype–phenotype cosegregation. High-resolution melting analysis followed by Sanger sequencing was used to screen for mutations in cadherin 2 ( CDH2 ) gene in unrelated genotype-negative patients with ARVC. In a 3-generation family, we identified by whole exome sequencing a novel mutation in CDH2 (c.686A>C, p.Gln229Pro) that cosegregated with ARVC in affected family members. The CDH2 c.686A>C variant was not present in >200 000 chromosomes available through public databases, which changes a conserved amino acid of cadherin 2 protein and is supported as the causal mutation by parametric linkage analysis. We subsequently screened 73 genotype-negative ARVC probands tested previously for mutations in known ARVC genes and found an additional likely pathogenic variant in CDH2 (c.1219G>A, p.Asp407Asn). CDH2 encodes cadherin 2 (also known as N-cadherin), a protein that plays a vital role in cell adhesion, making it a biologically plausible candidate gene in ARVC pathogenesis. Conclusions—: These data implicate CDH2 mutations as novel genetic causes of ARVC and contribute to a more complete identification of disease genes involved in cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.